THE PLACE OF FERGHANA ECONOMIC REGION IN NATIONAL ECONOMY OF UZBEKISTAN (ON THE EXAMPLE OF 50-70SS OF THE XX CENTURY) (Scientific journal of the Fergana State University, 2023)
The article presents the information on the place of Ferghana region in the national economy of Uzbekistan in the conditions of economic dependence of the former soviet republics after the II World War. The role of Ferghana region in the economic life of the country, agriculture, industry, in particular, cotton growing, silkworm breeding, along with the importance of the natural resources of the region. The structure of Ferghana economic region have been analyzed on the bases of the scientific literature and archival data.